Effective Thermal Conductivity of Cyclohexane-Based Nanofluids Containing Cerium Dioxide Nanoparticles with Chemisorbed Organic Shell - Bioucas, Francisco; Wu, Wenchang; Stiegler, Lisa; Peukert, Wolfgang; Walter, Johannes; Adschiri, Tadafumi; Yoko, Akira; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Thermophysics, 2025)
In the present study, the effective thermal conductivity λeff of nanofluids containing metal oxide nanoparticles with a chemisorbed organic shell was investigated experimentally and theoretically. The model systems synthesized by a continuous-flow hydrothermal method consist of cyclohexane as organic base fluid and dispersed nearly spherical cerium dioxide (CeO2) core nanoparticles with a decanoic acid shell chemically attached to their surface. From the differences between the hydrodynamic diameters of the two core–shell nanoparticle types with (8.6 or 9.1) nm determined by dynamic light scattering (DLS) and the nearly spherical CeO2 core diameters obtained by analytical ultracentrifugation (AUC) and transmission electron microscopy (TEM), an estimation for the thickness of the entire hydrodynamic layer around the particle core in the range of about (1.1 to 1.3) nm could be deduced. Experimental data for λeff of the nanofluids and the thermal conductivity of the base fluid λbf were determined with a steady-state guarded parallel-plate instrument (GPPI) with an expanded (k = 2) relative uncertainty of 0.026 at atmospheric pressure over a temperature range from (283.15 to 313.15) K in steps of 10 K. The measurement results for the thermal-conductivity ratio λeff ·λbf–1 are independent of temperature and increase with increasing volume fraction of the CeO2 core nanoparticles up to about 0.023. It was found that the experimental results can be described by the Hamilton–Crosser model within their experimental uncertainties for all temperatures investigated.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Cerium oxide; Core–shell nanoparticles; Effective thermal conductivity; Hydrodynamic diameter; Nanofluids; Parallel-plate method